Pemanfaatan Tepung Lemna sp. dan Enzim Non-Starch Polysaccharides (NSPs) Pada Pakan Ikan Tambakan (Helostoma temminckii) - Sefti Heza Dwinanti; Kekey Zakaria; Muhammad Amin; Madyasta Anggana Rarassari (Fakultas Kelautan dan Perikanan Universitas Udayana, 2023)
Lemna sp. is one of the local raw materials that can be used to substitute fish flour and soybean meal in fish feed formulation because its protein contain. However, protein plant-based in fish feed formulation need additional enzyme (exogenous) such as Non starch polysaccharides (NSP) enzyme which able to increase feed digestibility. The aim of this study is to determine the effect of NSP enzyme to Lemna sp. flour in feed formulation for kissing gouramy’s growth and feed efficiency. This research has been conducted at the Experimental Pond Laboratory, Aquaculture Study Program and Laboratory of Chemical and Microbiology of Agricultural Products, Department of Agricultural Technology, Faculty of Agriculture, Sriwijaya University. Juvenile kissing gourami 4±0,5 cm in length were used and culture in certain condition which was temperature 25-27 °C, pH 6, dissolved oxygen > 2.5 mgL-1 and ammonia <0.1 mgL-1. The Rovabio Excel AP10 T-Flex were used as NSP enzyme. Completely Randomized Design (CRD) was used with 4 treatments (Tn) and 3 replications, namely the addition of Lemna sp. flour 0% without enzyme (T0), addition of Lemna sp. flour 0% with enzyme (T1), addition of Lemna sp. flour 5% without enzyme (T2), addition of Lemna sp. flour 5% with enzyme (T3). NSP enzyme dose is 1 g/kg feed material. The results showed that T3 gave the best results with absolute weight growth 0.91 g, absolute length growth 0.63 cm, specific weight growth rate 1.35% day-1, specific length growth rate 0, 41% day-1, survival 100%, and feed efficiency 28.59%.